Implementation of the Balanced Scorecard as a Strategy in Improving the Quality of Education - Muhtar, Zainal; Y, Maria Susana; Wahyudin, H; Wasliman, Iim; Sauri, Sofyan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The basic need of someone who is classified as important is education. People can develop his intelligence, self-potential, skills and shape personality with an education. Through education, a person can also obtain information and knowledge to train and develop his character. One of the places where people can get education is school. Schools as educational institutions have the duty and responsibility to produce students with character, broad insight, acceptable to society, especially consumers or users and able to compete at a global level. To form quality students, of course, the educational institution itself must have qualified and qualified quality. To determine the performance of educational institutions, a measuring instrument is needed that can assess each process of the running of educational institutions. The Balanced Scorecard (BSC) is a measuring tool which is also one of the management systems used to measure the efficiency of the performance of the institution. In the application or implementation of BSC into educational institutions, it is necessary to pay attention to the elements and factors that are important so that the implementation is successful and able to improve the quality of educational institutions.